Role of cell death pathways in response to photodynamic therapy in gliomas - De Paula, Leonardo Barcelos; Primo, Fernando Lucas [UNESP]; Tedesco, Antonio Claudio (Taylor & Francis, 2017)
Deeper characterization of signaling pathways important in glioma growth is needed and may enable the development of new pharmacological agents, which could be utilized in new therapies for patients who do not respond to conventional antitumor therapies. Protein kinase B (PKB/Akt) and the transcription factor, nuclear factor kappa B (NF-kappaB), have garnered attention as potential targets for cell death induction and sensitization to chemotherapy in many tumor cell types such as lung cancer, ovarian cancer, and glioblastoma (Aggarwal, 2004; Kapoor et al., 2004; Sethi et al., 2007; Wu et al., 2008; Xu et al., 2009; Koul et al., 2010; Zanotto-Filho et al., 2010).